Impact of Tribal Sub Plan (TSP) Intervention on Yield and Economics of Chickpea Cultivation in Kurnool District of Andhra Pradesh - Jayalakshmi, V; Chaithanya, B H; Manjunath, J; Ahammad, S Khayum; Kamakshi, N; Rama Devi, S (Indian Journal of Extension Education, 2022)
To promote improved chickpea varieties along with profitable crop management technologies, Regional Agricultural Research Station (RARS), Nandyal organized demonstrations on chickpea improved varieties along with crop package of practices in 210 tribal farmer’s fields (84 ha) under Tribal Sub Plan during 2018-2021 in Kurnool district of Andhra Pradesh. The technology interventions included improved varieties (Nandyal Gram 49 and Nandyal Gram 119), seed treatment with vitavax power (1.5 g/kg seed), basal application of zinc sulphate, erection of pheromone traps @ 10/ha, prophylactic spray of neem oil and use of need based plant protection chemicals. The average yield of demonstration field with improved desi variety Nandyal Gram 49 (14.36 q/ha) was 19 per cent higher than the existing farmers practice (12.05 q/ha) and the average yield of 13.16 q/ ha was recorded with improved kabuli variety Nandyal Gram 119 which resulted in 7.78 per cent yield increase over farmers practice (JG11/Vihar) (12.21 q/ha). These demonstrations resulted not only in higher yield, but the higher net returns and cost benefits indicated the worth of improved varieties and scope for further spread of other technological interventions in farmers’ holdings.